Surnames and American Trademark Law - Michael Adams; Jennifer Westerhaus Adams (Names, 2005)
Abstract American law discourages trademark registration of words that look and sound like surnames, yet some surnames are trademarks or parts thereof. The controlling issue in determining whether a mark is “primarily merely a surname” is its primary significance to the purchasing public, but several factors contribute to this determination: (1) surname rareness; (2) personal relation to the surname; (3) alternate meanings; (4) whether the mark has the structure and pronunciation of a surname; and (5) the mark's style. Thus, rarer, semantically developed, transparently onomastic words have a better chance of trademark status: it is by no means easy to determine what counts as the look and sound of a surname. Trademark law inadvertently promotes onomastic discrimination. Because the mass of American consumers easily identifies Western European surnames, those names are better protected from commercial appropriation. The “look and sound of a surname,” after all, is culturally determined. As a result, the law both reflects and reinforces attitudes about what counts as a surname and what doesn't.